Mortality and causes of death across the systemic connective tissue diseases and the primary systemic vasculitides. (3rd October 2018) - Garen, Torhild; Lerang, Karoline; Hoffmann-Vold, Anna-Maria; Andersson, Helena; Midtvedt, Øyvind; Brunborg, Cathrine; Kilian, Karin; Gudbrandsson, Birgir; Gunnarsson, Ragnar; Norby, Gudrun; Chaudhary, Asad; Thoen, Jørn; et al.
Abstract: Objectives: Studies assessing relative mortality risks across the spectrum of systemic inflammatory rheumatic diseases are largely missing. In this study, we wanted to estimate standard mortality ratios (SMRs) and causes of death in an ethnically homogeneous cohort covering all major CTDs and primary systemic vasculitides (PSVs). Methods: We prospectively followed all incident CTD and PSV cases included in the Norwegian CTD and vasculitis registry (NOSVAR) between 1999 and 2015. Fifteen controls for each patient matched for sex and age were randomly drawn from the Norwegian National Population Registry. Causes of death were obtained from the National Cause of Death Register, death certificates and hospital charts. Results: The cohort included 2140 patients (1534 with CTD, 606 with PSV). During a mean follow-up time of 9 years, 279 of the patients (13%) died, compared with 2864 of 32 086 (9%) controls ( P < 0.001). Ten years after diagnosis, the lowest survival was 60% in dcSSc, 73% in anti-synthetase syndrome (ASS) and 75% in lcSSc. In the CTD group, the highest SMRs were observed in dcSSc (SMR 5.8) and ASS (SMR 4.1). In the PSV group, Takayasu arteritis (SMR 2.5) and ANCA-associated vasculitis (SMR 1.5) had the highest SMRs. Major causes of death were cardiovascular disease (CTD 27%, PSV 28%), neoplasms (CTD 25%, PSV 27%), chronic respiratory disease (CTD 20%, PSV10%) and infections (CTD 9%, PSV 16%). Conclusion: We observed premature deaths across the spectrum of CTDs and PSVs, with highest SMRs in dcSSc and ASS. The overall mortality was highest in the CTD group.